Neutrophil-Derived IL-6 Potentially Drives Ferroptosis Resistance in B Cells in Lupus Kidney - Zechen Wang; Jiajia Shen; Kun Ye; Jingjie Zhao; Shaoang Huang; Siyuan He; Yujuan Qin; Lingzhang Meng; Jie Wang; Jian Song (Mediators of Inflammation)
Ferroptosis resistance is vital for B cell development, especially in inflammatory diseases, yet the underlying mechanism is still unclear. In this study, based on the scRNA-seq technique and flow cytometry, we discovered a proportion of neutrophils exhibited upregulated expression of the IL-6 and correlated with the expression of IL-6 receptor and SLC7A11 from B cells in lupus kidney. Moreover, we identified that in lupus kidney, neutrophils could provide IL-6 to facilitate ferroptosis resistance in B cells via SLC7A11, and inhibition of SLC7A11 could significantly enhance ferroptosis in B cells and could decrease B cell proliferation. This study helps understand the crosstalk between neutrophils and B cells in the kidney in the development of lupus.